The Effect of Price Earning Ratio on Market Performance in Banking Companies on the Indonesia Stock Exchange - Rajindra, Rajindra (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
This study aims to determine and analyze the effect of Price Earning Ratio on market performance in banking companies on the Indonesia Stock Exchange. The sampling method based on the purposive sampling method, there are 14 banking companies that meet the requirements and as a sample in this study using a simple regression analysis tool. The results of the study show that the variable Price Earning Ratio (PER) has no significant positive effect on Market Performance, this situation illustrates that Price to Earning Ratio (PER) is one of the company's financial ratios that can influence stock prices more dominantly than EPS. Companies that have a high PER value will attract investors to buy shares. So that the demand for these shares will increase, this will push the stock price to rise. Therefore, it can be concluded that the higher the PER, the higher the level of investor confidence in the company's future, seen from the company's growth, it will push the stock price up.